A saúde mental faz o que não existe: para além do instituído, a formação do psicólogo para o cuidado em saúde mental no contexto da reforma psiquiátrica - Fabio Walace de Souza Dias (2018)
The main purpose of this study is to investigate and analyse what psychologists, who work at the Network for Psychosocial Care (RAPS) from the municipality of Ipatinga, in the state of Minas Gerais, think about their academic background and the meanings they give to it, while acting in the field of mental health. We also want to identify In which extent this academic background is, or it is not, responding to the practical challenges in the context of a Psychiatric Reform, which is being developed. As specific objectives, this study aims to describe and analyse the history of the RAPS from Ipatinga, that work as a stage for the ocurrence, or not, of certain discourses concerning academic background, as well as to investigate if there are possible discursive features that could be considered as education while acting, built throughout the work routine and also if there is an inventive education, in a perspective of deinstitutionalisation, established through individual actions of the own psychologists who work in the above-mentioned network, that goes beyond or that is aligned with both the academic background and the guidelines of the national mental health policy that guide the actions of the psychologists on duty. To do so, we used an intersection between methodological approaches that are different but integrative. As this is a piece of qualitative research in Social Psychology that comprehends the subjects/actors of the research as protagonists in building themselves and the context in which they are inserted into, we drew our inspiration from Ethnography and from the foucauldian contribution regarding Discourse Analysis (DA) aiming to aproach the research field as deeply as possible and to comprehend the dicourses produced concerning the academic background as products and producers of reality plural, polyphonic and located. Lastly, we endeavour, from the Institutional Analysis, analyze the involvement of the researcher, closely related to the theme of research at stake. In this perspective, as the main methodological procedure, we carried out open interviews with the psychologists who work at the RAPS from Ipatinga, as well as, observations and interactions with the investigated field. The interviews (that were constituted as the corpus of this piece of research) aligned with the interaction with the field and the involvement of the researcher demonstrated some aspects of the discourse about the academic background of the psychologists that act in the mental health area. We identified that according to the psychologist of the RAPS from Ipatinga, sometimes the academic background seems insufficient, when we consider mental health as a field of knowledge (political); sometimes it seems, critically, (in)sufficient when mental health emerge aligned with the clinical conduction of mental illnesses. Furthermore, the analysis of the discursive features about the academic background of the psychologists who work in mental health showed us the existence of formative strategies while working, that happen through the supportive exchange of experiences among the psychologists that work in the RAP from Ipatinga and professional colleagues that work in other places. Ultimately, we observed the existence of a minority discourse about the inventive education that is articulated with daily life and other knowledges and experieces not necessarily originating from the academy or from the practice in mental health per se, but they showed to be important to face the challenges in the daily work in the RAPS from Ipatinga.